Methodology for the Evaluation of Varietal Resistance to Haplaxius crudus, Vector of the Causal Agent of Lethal Wilt in Oil Palm in Colombia - Ivette Johana Beltrán-Aldana; Gladys Alejandra Romero-Guerrero; Eloina Mesa-Fuquen; Anuar Morales-Rodriguez (Insects)
Lethal Wilt is a limiting disease for oil palm cultivation in the eastern and central zones of Colombia. In the eastern zone, it caused the eradication of approximately 8700 ha of oil palm between 2010 and 2022, with economic losses of more than 185 million dollars. Studies conducted by Cenipalma reported that the pathogen causing this disease is Candidatus Liberibacter, which is possibly transmitted by Haplaxius crudus (Van Duzee). The adults feed on the foliage of the palms and move between them, spreading the pathogen in the plantation. A strategy to contribute to the management of LW is establishing cultivars resistant to the insect vector; however, no resistant cultivars or sources of resistance have been identified in the country’s commercial cultivars or germplasm collections. Therefore, this work aimed to design and validate a methodology to characterize the oil palm genotypes Elaeis guineensis and Elaeis oleifera and interspecific OxG hybrids against adults of H. crudus, evaluating resistance through antixenosis and antibiosis to identify genotypes with possible sources of resistance. An arena with leaflets of the different genotypes in free-choice tests was used to assess antixenosis. For antibiosis, entomological sleeves were installed on the palm leaves, which were infested with adults of H. crudus from a breeding unit. The results of antixenosis and antibiosis in both the first phase (design) and the second phase (validation) indicated greater preference and survival for the genotypes of E. guineensis and lower preference and survival for the interspecific hybrids and E. oleifera. In the genotype E. guineensis, the average mortality was reached after 30 days, while in E. oleifera and the hybrids, it occurred between the third and fourth days. The results of this research provide a reproducible methodology for the evaluation of oil palm germplasms against H. crudus and sucking insects for the selection of sources of resistance for incorporation into breeding programs.